1989
DOI: 10.1007/bf02926481
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous nephrostomy in pyonephrosis

Abstract: A series of 76 pyonephrotic kidneys in 73 patients were drained by percutaneous nephrostomy (PN) tube and examined to evaluate the contribution of this technique to the treatment of pyonephrosis. In 71 patients, clinical symptoms disappeared 24-48 h after the procedure. Two patients died from sepsis subsequent to anuria and underlying malignancy. Once the acute phase had remitted, interventional procedures were carried out in 39 cases, and constituted the definitive therapy in 36. In 32 cases, elective surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The co-existence of azotemia and pyonephrosis increases the urgency as well as value of percutaneous Nephrostomy. Camunez et al also observed that following PCN in pyonephrosis clinical symptoms disappeared in 24 -48 h after the procedure and once the acute phase was over definitive surgery could be carried out (9).…”
Section: Commentsmentioning
confidence: 97%
“…The co-existence of azotemia and pyonephrosis increases the urgency as well as value of percutaneous Nephrostomy. Camunez et al also observed that following PCN in pyonephrosis clinical symptoms disappeared in 24 -48 h after the procedure and once the acute phase was over definitive surgery could be carried out (9).…”
Section: Commentsmentioning
confidence: 97%
“…(7) Likewise St.Lezin et al salvaged 78.3% of 23 pyonephrotic kidneys drained percutaneously. (8) In fact, percutaneous nephrostomy was shown to decrease mortality associated with gram-negative sepsis due to obstruction of the urinary tract (7.4% mortality) compared to treatment with antibiotics and steroids alone (40%) or surgical decompression. (9) The development of internal ureteral stents that could be placed cystoscopically provided an alternative to percutaneous renal drainage in cases of ureteral obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…(11) Improvements in stent design resulted in greater ease of placement and more secure positioning. (12,13,14) However, despite these improvements, the use of ureteral stents for drainage of infected, obstructed kidneys was sporadic and reports in the literature were few (8,15) . Indeed, in 1 series of 23 patients with pyonephrosis treated with percutaneous nephrostomy a previous retrograde attempt at drainage had failed in 30%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations